Leigh Syndrome—TUFM Gene Mutation as a New Probable Genetic Marker: A Case Report - Jain, Nikhil; Bhargava, Harshit; Dwivedi, Deepak (Journal of Pediatric Epilepsy, 2020)
Leigh's syndrome is a rare neurodegenerative disorder which is of autosomal recessive or mitochondrial inheritance. Global incidence is 1 in 40,000 although very few cases have been reported from India. Respiratory failure is the main cause of death in these children. An 8-year-old female presented to pediatric intensive care unit with chief complaints of seizure (generalized tonic-clonic seizure type), generalized weakness, and swelling, which on MRI and genetic study was diagnosed as Leigh syndrome or Leigh like syndrome. Genetic study revealed a new TUFM gene mutation. Patient improved over the time, oxygen was weaned gradually, and nasogastric tube feeding started, and patient shifted to ward, and discharged on oral antiepileptic therapy. A genetic counseling, early diagnosis, better understanding of disease can result in good seizure control and improved quality of life of these patients. TUFM gene mutation must be considered as a new probable genetic marker.
Keywords: subacute necrotizing encephalomyelopathy; mitochondrial inheritance; TUFM gene